A European Respiratory Society technical standard: exhaled biomarkers in lung disease. Issue 4 (27th April 2017) - Horváth, Ildiko; Barnes, Peter J.; Loukides, Stelios; Sterk, Peter J.; Högman, Marieann; Olin, Anna-Carin; Amann, Anton; Antus, Balazs; Baraldi, Eugenio; Bikov, Andras; Boots, Agnes W.; Bos, Lieuwe D.; et al.
Breath tests cover the fraction of nitric oxide in expired gas ( F eNO ), volatile organic compounds (VOCs), variables in exhaled breath condensate (EBC) and other measurements. For EBC and for F eNO, official recommendations for standardised procedures are more than 10 years old and there is none for exhaled VOCs and particles. The aim of this document is to provide technical standards and recommendations for sample collection and analytic approaches and to highlight future research priorities in the field. For EBC and F eNO, new developments and advances in technology have been evaluated in the current document. This report is not intended to provide clinical guidance on disease diagnosis and management. Clinicians and researchers with expertise in exhaled biomarkers were invited to participate. Published studies regarding methodology of breath tests were selected, discussed and evaluated in a consensus-based manner by the Task Force members. Recommendations for standardisation of sampling, analysing and reporting of data and suggestions for research to cover gaps in the evidence have been created and summarised. Application of breath biomarker measurement in a standardised manner will provide comparable results, thereby facilitating the potential use of these biomarkers in clinical practice. ERS technical standard: exhaled biomarkers in lung disease http://ow.ly/mAjr309DBOP